Post-Merger Digital-Media Content Management - Tantri Dwi Rahmawati; Reza Safitri; Rachmat Kriyantono (Sekolah Pascasarjana Universitas Brawijaya, 2020)
This study aimed to analyze the process of managing digital media content after the KapanLagi Networks merged. The research study adopted a descriptive-qualitative approach. The informants were selected using a purposive sampling method. The data were collected through participant observation and in-depth interviews. The results found merger strategy had a positive impact on KapanLagi Networks. The merger strategy succeeded in providing an opportunity for KapanLagi Networks to develop its content. Content management of KapanLagi Networks is influenced by several factors, including 1) professionalism and target demands; (2) user behavior; (3) profit orientation; (4) analytic tools and social media; (5) capitalist ideology; (6) implementation of digital journalism and multimedia journalism; (7) editorial policy. These factors indicate merger integration does not always produce content uniformity but also encourages content diversity.